1982
DOI: 10.1007/bf00987764
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone components of the turnip moth,Agrotis segetum

Abstract: Analysis of female abdominal tips ofAgrotis segetum by means of GC-MS showed the presence of 13 aliphatic acetates and alcohols. (Z)-7-Dodecenyl acetate was found to be the main component in the extracts at amounts of about 1 ng/female. (Z)-9-Tetradecenyl acetate and (Z)-7-dodecenol were present to the extent of 49 and 19%, respectively, of the main component. Minor components could be identified as decyl acetate, (Z)-5-decenyl acetate, dodecyl acetate, (Z)-9-dodecenyl acetate, tetradecyl acetate, a tetradecen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Except for the four pheromone components and two behavioural antagonists, we also included decyl acetate (10:OAc) as a stimulus for the oocytes, a component in the female sex pheromone gland extract that could elicit electroantennogram (EAG) activity, and early on was considered to be essential for full behavioural activity in the laboratory behavioural bioassay [11]. Thus seven chemicals were applied to the injected oocytes successively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the four pheromone components and two behavioural antagonists, we also included decyl acetate (10:OAc) as a stimulus for the oocytes, a component in the female sex pheromone gland extract that could elicit electroantennogram (EAG) activity, and early on was considered to be essential for full behavioural activity in the laboratory behavioural bioassay [11]. Thus seven chemicals were applied to the injected oocytes successively.…”
Section: Resultsmentioning
confidence: 99%
“…A. segetum makes use of a sex pheromone consisting of four structurally similar sex pheromone components ( Z )-5-decenyl, ( Z )-5-dodecenyl, ( Z )-7-dodecenyl and ( Z )-9-tetradecenyl acetates ( Z 5-10:OAc, Z 5-12:OAc, Z 7-12:OAc, and Z 9-14:OAc), that are specifically perceived by distinct types of sensilla trichodea in males. A detailed single-sensillum recording study demonstrated that for Z 5-10:OAc-type sensilla (Type-1 sensilla) there are at least three subtypes, each possessing a different tuning profile to other components [11-13]. The projection of olfactory receptor neurons (ORNs) to different regions of the macroglomerular complex is also quite specific [14] but potential differences in the projection of ORN subtypes were not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Swedish than to the Zimbabwean blend could be ascribed to the dose effect, since the amount of components in the Swedish blend is higher than that in the Zimbabwean blend. However, we also found neurons that responded preferentially to the Zimbabwean blend, i.e., a higher response to a lower dose, a phenomenon that has to be interpreted as a true blend effect.…”
Section: Discussionmentioning
confidence: 96%
“…Previous study has shown that there is very little pheromone production of the turnip moth during the photophase (Löfstedt, 1984). One day after emergence, females were put under DD and pheromone production were examined for 3 consecutive days at the same time as when females were kept in LD cycle.…”
Section: Pheromone Analysesmentioning
confidence: 99%